2020
DOI: 10.2196/23868
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Improvements in Systemic Lupus Erythematosus Derived from a Digital Therapeutic Plus Tele-Health Coaching Intervention: Randomized Controlled Pilot Trial

Abstract: Background Systemic lupus erythematosus (SLE), a systemic autoimmune disease with no known cure, remains poorly understood and patients suffer from many gaps in care. Recent work has suggested that dietary and other lifestyle factors play an important role in triggering and propagating SLE in some susceptible individuals. However, the magnitude of influence of these triggers, how to identify pertinent triggers in individual patients, and whether removing these triggers confers clinical benefit is u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…An increasing body of evidence supports the use of mobile apps in IBD, as in other chronic diseases [ 15 , 16 ], to increase quality of life and medication adherence, to improve patient outcomes, and to decrease health care costs in chronic diseases such as type 2 diabetes [ 17 ], chronic obstructive pulmonary disease [ 18 , 19 ], and chronic heart failure [ 20 , 21 ]. In IBD, mobile health (mHealth) interventions to monitor patients have been shown to reduce health care visits by 33% and reduce hospital admissions without increasing disease activity or decreasing patient satisfaction [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of evidence supports the use of mobile apps in IBD, as in other chronic diseases [ 15 , 16 ], to increase quality of life and medication adherence, to improve patient outcomes, and to decrease health care costs in chronic diseases such as type 2 diabetes [ 17 ], chronic obstructive pulmonary disease [ 18 , 19 ], and chronic heart failure [ 20 , 21 ]. In IBD, mobile health (mHealth) interventions to monitor patients have been shown to reduce health care visits by 33% and reduce hospital admissions without increasing disease activity or decreasing patient satisfaction [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five studies revealed better outcomes with remote monitoring, especially an improved quality of life,11 13 fatigue and pain,13 higher numbers of patients reaching remission,16 lower number of patient visits14 and reduced travel distance 21 22. Five studies found no differences between the investigated remote intervention and the comparator group11 12 14 15 17 18 (Berdal et al only for patient beliefs).…”
Section: Resultsmentioning
confidence: 98%
“…In the 12 studies on efficacy, outcomes investigated were highly heterogeneous. Eleven different patient-reported outcome measures (PROMs) were reported, assessing generic quality of life,11–15 disease severity14 16 and activity,17 function,12 14 fatigue,13 pain13 and patient beliefs 11. Disease activity was captured by composite scores in five studies 12 14–17.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a Phase 4 multi-centre RCT examining the efficacy and safety of Acthar Gel in persistently active SLE patients demonstrated significant and clinically meaningful improvements in LupusQoL scores for the pain, planning, and fatigue domains in those who had higher disease activity levels [36]. Lastly, the remaining two clinical trials found that upper limb exercises [37] and a digital therapeutic plus telehealth coaching intervention [38] led to significant and clinically meaningful improvements in HRQoL as measured by LupusQoL scores. LupusQoL was not designed for use in the clinical setting and has not been studied as a PRO for use in routine care.…”
Section: Lupusqolmentioning
confidence: 99%